2008
DOI: 10.3892/mmr_00000029
|View full text |Cite
|
Sign up to set email alerts
|

c-Met expression in primary tumors and their corresponding distant metastases

Abstract: Abstract. c-Met is a receptor tyrosine kinase that has been implicated in the pathogenesis and growth of a wide variety of human malignancies, including CRC, but its role in metastasis is largely unknown. We compared c-Met expression in primary human colorectal carcinomas and distant metastases from the same patients. Formalin-fixed paraffin-embedded tissue samples from 69 colorectal cancer patients were obtained. The protein expression of c-Met was evaluated immunohistochemically using a commercial antibody. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Two studies showed that c-MET protein expression tended to be decreased in distant metastases compared to their corresponding primary tumors. ( 5 , 17 ) In contrast, Voutsina et al . ( 18 ) observed that c-MET expression tended to be increased in distant metastases compared to their corresponding primary tumors.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Two studies showed that c-MET protein expression tended to be decreased in distant metastases compared to their corresponding primary tumors. ( 5 , 17 ) In contrast, Voutsina et al . ( 18 ) observed that c-MET expression tended to be increased in distant metastases compared to their corresponding primary tumors.…”
Section: Discussionmentioning
confidence: 96%
“…The frequency of expression of c-MET protein in CRC as detected by immunohistochemistry (IHC) has been reported to be between 59.4% and 81.1%; it is associated with advanced tumor stages and poor clinical outcomes. ( 5 )– ( 8 ) Similar to c-MET protein expression, c-MET gene amplification is linked to disease metastases. ( 9 , 10 ) The HGF/c-MET pathway is also well-known to be associated with liver regeneration and the development of normal organs, such as the placenta, muscle and the central nervous system.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the relatively small sample size or to actual lack of biological difference. In a study by Ljuslinder et al, 67% of primary CRC tumours (n ϭ 64) showed high HER3 expression and there was a correlation with expression of HER3 in corresponding lymph node metastases, both membrane and cytoplasmic staining were considered [21]. In a study by Wei et al including 49 patients, they reported a HER3 expression in 16% of the primary CRC and 18% in corresponding lymph node metastases.…”
Section: Discussionmentioning
confidence: 98%
“…Cytoplasmic or background staining was not graded. The lower limit of positive expression of HER3 was set at 10% stained CRC cells according to literature [10,20,21]. The entire slide of the tumour or metastasis was evaluated.…”
Section: Scoring Systemmentioning
confidence: 99%